The Role of BMT Artha Amanah in Achieving Sustainable Development Goals through the Integration of Maal-Tamwil Functions: An Equity Theory Perspective - Komairah Angriani; Sartini Wardiwiyono (Edusoshum : Journal of Islamic Education and Social Humanities, 2026)
This study aims to analyze the role of BMT Artha Amanah in supporting the achievement of the Sustainable Development Goals (SDGs), specifically SDG 1 (no poverty), SDG 2 (zero hunger), and SDG 8 (decent work and economic growth), through the integration of the maal and tamwil functions. This study used a qualitative case study approach, involving six informants: five members and one BMT manager. Data were collected through in-depth interviews, observations, and documentation, and then analyzed using data reduction, data presentation, and conclusion-drawing techniques. The results reveal three main findings. First, productive financing, combined with structured mentoring, increases members’ monthly income and strengthens MSME capacity. Second, optimizing the maal functions through ZISWAF distribution provides a social safety net for vulnerable members during emergencies. Third, the integration of maal and tamwil functions promotes holistic welfare covering economic, social, and spiritual dimensions. However, the program's effectiveness is still constrained by members’ low financial literacy in managing business cash flow. The novelty of this study lies in extending Equity Theory within the context of Islamic microfinance by demonstrating that distributive justice is reflected not only in financial profit-sharing mechanisms but also in equal access to services, empowerment, and managerial assistance. In practice, this study offers a sustainable empowerment model through the synergy between social and commercial functions to support SDG localization.